Pengaruh ESG terhadap Kinerja Perusahaan: Moderasi Board Gender Diversity - Ulfa, Siti Naziyatul; Rahman, Annisaa (Journal of Economics and Management Scienties, 2024)
Company performance is a metric in assessing the level of success of a company in a certain period. to maintain good company performance, companies need to manage core business, namely building good relationships with stakeholders. For investors as stakeholders, the availability of information presented by the company is very important to decide on the right capital allocation and avoid the risks that occur. With the encouragement from the government and investors as stakeholders, more and more companies want to provide a clear picture of corporate practices and responsibilities, one of which is by disclosing environmental, social and corporate governance (ESG) aspects. The purpose of this study to provide empirical evidence regarding the influence of ESG on company performance, provide empirical evidence regarding the role of board gender diversity on the influence of ESG on the performance of companies listed on the Stock Exchange in Indonesia and Germany in 2018-2022. The sampling technique in this study was purposive sampling. Data was taken from Thomsonreuters and this study used panel data regression analysis with STATA 17. The results of this study found that ESG has no effect on company performance in Indonesia. The results of further research found that ESG has a negative effect on company performance in Germany. This study found that board gender diversity plays a role in encouraging ESG activities to improve firm performance in Germany.